The Implementation of E-books Based on Technological Pedagogical Content Knowledge (TPACK) to Improve Multi-Representation Ability and Physics Students' Conceptual Understanding - Masrifah, Masrifah; Amiroh, Dewi; Samsudin, Achmad; Taib, Suryani; Balulu, Nasrun; Costu, Bayram (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2025)
The aim of the research is to examine the multi-representation abilities and conceptual understanding of physics students as the impact of implementing e-books based on TPACK. The reality on the field shows that the representation ability of students at various education levels is still inadequate.  The research design used in this research is a group pretest-posttest design. The subjects involved in this research were 30 students from the Physics Education Study Program at Universitas Khairun (Unkhair) and 34 students from the Physics Education Study Program at the Universitas Pendidikan Indonesia (UPI). The instrument used in this research, namely multi-representation questions, was adopted from the Representation-Force Concept Inventory (R-FCI) instrument with a modified presentation in the form of Google Form so that it is more in line with current developments in educational technology. The results of the research show that the multi-representation abilities and conceptual understanding of in-service physics teachers at Unkhair have increased respectively by 0.43 and 0.56 in the moderate category. after the learning process using e-books based on TPACK. Meanwhile, in-service physics teachers at UPI have increased respectively by 0.89 and 0.87 in the high category. This shows that the physics e-book based on TPACK developed can improve students' multi-representation abilities and understanding of concepts as expected.